Inborn coagulation factors are more important cardiovascular risk factors than high LDL-cholesterol in familial hypercholesterolemia. (December 2018) - Ravnskov, Uffe; de Lorgeril, Michel; Kendrick, Malcolm; Diamond, David M.
Abstract: High low-density-lipoprotein cholesterol (LDL-C) is routinely described as the main cause of cardiovascular disease (CVD) in familial hypercholesterolemia (FH). However, numerous observations are in conflict with Bradford Hill's criteria for causality: a) degree of atherosclerosis is not associated with LDL-C; b) on average the life span of people with FH is about the same as for other people; c) LDL-C of people with FH without CVD is almost as high as in FH patients of the same age with CVD; and d) questionable benefit or none at all have been achieved in the controlled, randomized cholesterol-lowering trials that have included FH individuals only. Obviously, those individuals with FH who suffer from CVD may have inherited other and more important risk factors of CVD than high LDL-C. In accordance, several studies of FH individuals have shown that various coagulation factors may cause CVD. Equally, some non-FH members of an FH kindred with early CVD, have been found to suffer from early CVD as well. Cholesterol-lowering has only been successful in an animal experiment by using probucol, which has anticoagulant effects as well. We conclude that systematic studies of all kinds of risk factors among FH individuals are urgently required, because today millions of people with FH are treated with statins, the benefit of which in FH is unproven, and which have many serious side effects. We predict that treatment of FH individuals with elevated coagulation factors with anticoagulative drugs is more effective than statin treatment alone.